Activated Ion ETD Performed in a Modified Collision Cell on a Hybrid QLT-Oribtrap Mass Spectrometer - Ledvina, Aaron R. (2013)
We describe the implementation and characterization of activated ion electron transfer dissociation (AI-ETD) on a hybrid QLT-Orbitrap mass spectrometer. AI-ETD was performed using a collision cell that was modified to enable ETD reactions, in addition to normal collisional activation. The instrument manifold was modified to enable irradiation of ions along the axis of this modified cell with IR photons from a CO(2) laser. Laser power settings were optimized for both charge (z) and mass to charge (m/z) and the instrument control firmware was updated to allow for automated adjustments to the level of irradiation. This implementation of AI-ETD yielded 1.6 fold more unique identifications than ETD in an nLC-MS/MS analysis of tryptic yeast peptides. Furthermore, we investigated the application of AI-ETD on large scale analysis of phosphopeptides, where laser power aids ETD, but can produce b- and y-type ions due to the phosphoryl moiety's high IR adsorption. nLC-MS/MS analysis of phosphopeptides derived from human embryonic stem cells using AI-ETD yielded 2.4 fold more unique identifications than ETD alone, demonstrating a promising advance in ETD sequencing of PTM containing peptides.